Identifikasi Sebaran dan Jenis Sesar Lokal di Sekitar Sesar Waipoga Dengan Analisis Anomali Gravitasi - Hafidz Syarifuddin; Mahmud Yusuf (Jurnal Teori dan Aplikasi Fisika, 2024)
Nabire Regency is located on the bird's neck of the island of Papua with a history of high seismicity. The Waipoga fault as a major fault was recorded to have caused the Nabire earthquake on November 26, 2004 with a magnitude of 7.2 Mw. Around the Waipoga fault there are small faults that are suspected to be faults. This research aims to identify the presence of suspected faults around the Waipoga Fault using the gravity method. The gravity data uses GGMPlus global satellite data in combination with topographic data from DEMNAS. The research uses surfer software to display the distribution of simple bouger anomalies, residual regional anomalies, and derivative analysis. The anomaly value obtained shows that the Nabire Regency area is predominantly composed of hard rock with a density of 2.7187 grams / cm3. The high density of subsurface constituent rocks results in a dominant positive simple bouger anomaly (SBA) value, with a value range between -10 mGal to 95 mGal. From the results of the FHD (Firts Horizontal Derivative) and SVD (Second Vertical Derivative) analysis, it shows a clear density contact boundary so that the fault line can be drawn in two segments. Fault segment A has a northeast-southwest (NE-SW) orientation with a rising fault mechanism. Segment B shows a descending fault that has a meandering shape towards the northwest-southeast (NW-SE).   Keywords: Gravity anomaly, FHD, SVD, Waipoga Fault